Flight-to-quality and contagion in the European sovereign debt crisis: The cases of Portugal and Greece - Pereira, I. P. (2022)
Purpose: The purpose of this paper is to analyze the co-movements between the Portuguese, Greek, Irish and German government bond markets after the subprime crisis (2007 to 2013), with a special focus on the European sovereign debt crisis. It aims to assess the existence of contagion between the Portuguese, Greece and Irish bond markets and to explore the phenomenon of flight-to-quality from the Portuguese and Greek bond markets to the German market. Design/methodology/approach: The analysis is undertaken using a DCC-GARCH model with daily data for 10-year yield government bonds. The change in correlation from the stable periods to the crisis periods is used to identify contagion or flight-to-quality. Findings: Results suggest that there was contagion between the Greek and Portuguese markets, and to a lesser extent between the Irish and Portuguese markets. During most of the identified crisis periods, there are evident flight-to-quality flows from the Portuguese and Greek bond markets to the German market. Originality/value: This paper contributes to the literature by applying the methodology DCC-GARCH to several crisis episodes for the analysis of contagion and flight-to-quality during the European sovereign debt crisis.